Implementasi Program Berbasis Keislaman dalam Pemberdayaan Masyarakat dan Pengembangan Pendidikan Anak di Mushola Al-Mannar, Desa Talang Tinggi - Hendri, Jul; Anggraini, Reza; Oktavia, Lola; Azhara Wijaya, Vanessa; Wistira, Wistira; Dwi Fitria, Veny; Lestari, Via; Madani, Liota; Fitriani Batubara, Desi; Sulistiono, Anjar; Novika Osaren, Virenti; Sinta, Sinta (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Community Service Program (KKN) is a means to apply and develop science and technology outside the campus environment, which is carried out within a certain time period, work mechanism, and requirements. Community Service Program organized by universities aims to enrich and improve the quality of student education, as well as provide greater added value to higher education. Through the implementation of this KKN, it is expected that students can develop their social and personality competencies. This journal examines the implementation of the Islamic-based Community Service Program (KKN) at the Al-Mannar Mosque, Talang Tinggi Village, West Seluma District, Seluma Regency, Bengkulu Province. This program aims to empower the community through children's education and social activities integrated with Islamic values. This study uses participatory methods and program evaluation to assess the impact of the activities carried out. The results of this program show an increase in religious awareness among children and economic empowerment through Islamic activities. Strengthening the role of the mosque as a center for community activities is also an important achievement